2023
DOI: 10.1021/acs.jmedchem.2c01957
|View full text |Cite
|
Sign up to set email alerts
|

Perspective for Discovery of Small Molecule IL-6 Inhibitors through Study of Structure–Activity Relationships and Molecular Docking

Abstract: ) is a proinflammatory cytokine that plays a key role in the pathogenesis and physiology of inflammatory and autoimmune diseases, such as coronary heart disease, cancer, Alzheimer's disease, asthma, rheumatoid arthritis, and most recently COVID-19. IL-6 and its signaling pathway are promising targets in the treatment of inflammatory and autoimmune diseases. Although, anti-IL-6 monoclonal antibodies are currently being used in clinics, huge unmet medical needs remain because of the high cost, administration-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 145 publications
0
4
0
Order By: Relevance
“…Inflammation is the basic defense mechanism of immunization and can protect against injuries caused by harmful stimuli. , Several cell types such as macrophages and T cells together with extracellular mediators of the immune system are keys for the regulation of the inflammatory process . As pro-inflammatory cytokines, IL-6 and IL-1β are produced by multifarious cells and play an important role in the regulation of inflammation, immune responses, and the acute-phase reaction. , Particularly, IL-6 was deemed as the key mediator of chronic disease pathogenesis in a wide range of pathological inflammatory situations, including end-stage renal disease and rheumatoid arthritis . Therefore, compounds which can regulate production of IL-1β and IL-6 in LPS-stimulated macrophages have the potential to be developed into novel anti-inflammatory drugs.…”
Section: Resultsmentioning
confidence: 99%
“…Inflammation is the basic defense mechanism of immunization and can protect against injuries caused by harmful stimuli. , Several cell types such as macrophages and T cells together with extracellular mediators of the immune system are keys for the regulation of the inflammatory process . As pro-inflammatory cytokines, IL-6 and IL-1β are produced by multifarious cells and play an important role in the regulation of inflammation, immune responses, and the acute-phase reaction. , Particularly, IL-6 was deemed as the key mediator of chronic disease pathogenesis in a wide range of pathological inflammatory situations, including end-stage renal disease and rheumatoid arthritis . Therefore, compounds which can regulate production of IL-1β and IL-6 in LPS-stimulated macrophages have the potential to be developed into novel anti-inflammatory drugs.…”
Section: Resultsmentioning
confidence: 99%
“…One such application involves predicting the binding modes between a ligand and its target, enabling the ranking of compounds based on their docking scores and establishing a relationship between these scores and potential activity [ 32 ]. The visualization of interactions obtained from docking studies can further assist in improving the affinity characteristics of the ligands under investigation [ 33 ]. Consequently, a thorough molecular docking analysis was conducted to assess the binding affinity of the best cytotoxic compounds, compounds 8a , 8h , and 8i , towards VEGFR2.…”
Section: Resultsmentioning
confidence: 99%
“…[10] The docking study indicated that MDL-A interacts with gp130 and thereby interferes in IL-6 binding to gp130 resulting in inhibition of IL-6 signaling. [11] The Brassica bioactive compounds were found to have antiinflammatory activity and showed a reduction in IL-6 levels. [12] JAK kinase which is part of the IL-6 signaling pathway has been targeted for the development of inhibitors in recent times.…”
Section: Introductionmentioning
confidence: 99%